Extremely Low Doses of X-Radiation can Induce Adaptive Responses in Mouse Prostate - Tanya K. Day; Guoxin Zeng; Antony M. Hooker; Madhava Bhat; David R. Turner; Pamela J. Sykes (SAGE Publishing, 2007)
The pKZ1 mouse chromosomal inversion assay is the only assay that has detected modulation of a mutagenic endpoint after single whole body X-irradiation with doses lower than 1 mGy. A non-linear dose response for chromosomal inversion has been observed in spleen and prostate between 0.001 mGy and 10 mGy, with doses between 0.005-0.01 mGy causing an increase in inversions and doses between 1-10 mGy causing a reduction below spontaneous inversion frequency. An adaptive response is a decreased biological effect induced by a low radiation dose. Adaptive responses contradict the linear-no-threshold model of risk estimation. We demonstrated that very low (0.001 mGy, 0.01 mGy, 1 mGy and 10 mGy) doses of X-radiation induced a chromosomal inversion adaptive response as measured by a reduction in the frequency of subsequent high dose (1000 mGy) induced inversions in prostate. These are the lowest X-radiation doses reported to induce an adaptive response for any endpoint. Adaptive response experiments were also performed where the high dose was administered four hours prior to a low dose of 0.01 mGy or 10 mGy. In both cases an adaptive response was observed. Identification of the modifying factors involved in the adaptive response may provide candidates for radioprotection.